Pemanfaatan Influencer Endorsement Sebagai Strategi Dalam Meningkatkan Brand Awareness Pada UMKM Onies Brownies - Ghina Misrina Mardhotillah; Rani Sukmadewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research discusses UMKM Onies Brownies, which is a micro, small, and medium-sized enterprise that specializes in culinary products, especially baked brownies. This research discusses marketing strategies that can increase brand awareness to improve the competitiveness and business capacity of Onies Brownies. This research uses a qualitative research method with a descriptive approach and is carried out accurately, factually, and systematically. The results show that UMKM Onies Brownies has successfully achieved an increase in business development with quality products, marketing strategies, and a wide network of partners. Continuous innovation is an important aspect for UMKM like Onies Brownies because it allows them to remain relevant and competitive in a constantly changing market. The article also discusses the obstacles faced by UMKM in their business activities and strategies that can be taken to overcome these obstacles. Keywords: Micro, Small, and Medium-Sized Enterprises, Marketing, Brand Awareness, Influencer, Endorsement.